(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The growth of the IT Industry is drastically influenced by the vital factor Human Resources, asthe availability of skilled and trained talent pool is imperative. SHCM practices and strategies followed bythe IT companies are designed to attract and retain the professionals and are formulated to meet thecurrent market conditions. Strategic Options for the Indian Information Technology Industry, Theevolution of corporate strategy has been hastened by the IT revolution. The only constant in life ischange, and it’s not hard to see why. Similarly, it appears to be the sole constant in the IT industry.Strategic Human Capital Management in IT companies is very important to mobilize the talentedemployees to accomplish the assigned job in the stipulated time. The organizations take special care forthe Strategic Human Capital Management practices for their increase in the productivity and profitability.